2006
DOI: 10.2747/0272-3646.27.2.155
|View full text |Cite
|
Sign up to set email alerts
|

Directional Characteristics of Potentially Damaging Wind Gusts in the Southeast United States

Abstract: Annual estimated storm damage in the United States is seven billion dollars. Much of that damage is caused by tree blowover that is induced by high wind gusts. The prevailing directions of these wind gusts dictate the zones around structures in which trees may potentially fall and cause damage. To gain a better understanding of hazardous wind gusts, this research examines the directional component of wind gusts in the Southeast United States. Regional patterns of wind gusts are identified and tied to atmospher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…The minimal number of HWEs was also supported by stations located in the southeastern United States. Martin and Konrad () found that wind gusts greater than 17.9 m/s (~40 mph) was rarely reported in the southeastern United States during 1995–2003. The HWE regional groupings described in this study is supported by Letson et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The minimal number of HWEs was also supported by stations located in the southeastern United States. Martin and Konrad () found that wind gusts greater than 17.9 m/s (~40 mph) was rarely reported in the southeastern United States during 1995–2003. The HWE regional groupings described in this study is supported by Letson et al .…”
Section: Discussionmentioning
confidence: 99%
“…The final wind direction grouping found for the southeastern United States was highly variable. Martin and Konrad () determined a differing gust wind pattern for 20 ASOS stations located in the Appalachian Mountains, Piedmont, and coastal southeastern United States between 1995 and 2003. The study described four geographic wind patterns: (a) northeast and southwest wind direction for northeastern coast (Virginia and North Carolina), (b) westerly orientation for the southeast coast; (c) southwest direction was prevalent for Piedmont stations, with a secondary easterly component documented towards the northeast; and (d) mountainous stations observed high‐wind gust related to orographic and topographic settings.…”
Section: Discussionmentioning
confidence: 99%
“…Niziol and Paone’s (2000) 20‐year analysis for Buffalo, NY found a peak in the frequency of events in January and a preference for winds from the southwest‐to‐west direction, along Lake Erie. Martin and Konrad (2006), examining strong wind gusts over 8 years in the Southeast USA (of which only 8% were convective in nature), discovered a March peak. Their analysis also revealed a south–southwest to west–southwest directional preference at several surface observing stations.…”
Section: Non‐convective High Wind Climatologiesmentioning
confidence: 99%
“…In addition, nonconvective winds occur over much larger spatial and temporal scales compared to thunderstorm phenomena, making it difficult to identify specific "storm reports" required to generate a climatology. A few studies are beginning to emerge examining nonconvective wind phenomena (e.g., Niziol and Paone 2000;Browning 2004;Knox 2004;Martin and Konrad 2006), but these investigations tend to focus exclusively on midlatitude cyclone winds and/or specific locales. Hence, there is a need for future research to continue to evaluate the climatology and risk of nonconvective wind phenomena.…”
Section: February 2008 N O T E S a N D C O R R E S P O N D E N C Ementioning
confidence: 99%